Effectiveness of Curry Leaf Extract Gel on Fibroblast Cell Count in Periodontitis-Induced Wistar Rats - Nuzulul Ismi; Dewi Saputri; Sunnati Sunnati; Zulfan M. Alibasyah; Dara Yunita Arsika (Universitas Muhammadiyah Semarang, 2026)
Background: Periodontitis is an inflammatory condition affecting the tissues that support the teeth, triggered by bacterial plaque, which leads to the ongoing and gradual destruction of the periodontal ligament and alveolar bone. Gingival recession and periodontal pockets are characteristics of clinical features. The disparity in the interaction between bacteria and the host's immune response can inhibit fibroblast proliferation, resulting in periodontal tissue damage. Important phytochemical components found in curry leaves (Murraya koenigii) include flavonoids, tannins, alkaloids, and saponins. Flavonoids and saponins effectively inhibit the growth of bacterial colonies in periodontal pockets.Objective: The research aims to assess the effect of curry leaf extract gel on the level of fibroblast cells in periodontitis.Methods: A posttest-only control group design was used in the experimental laboratory. Subjects were categorized into 3 categories: a treatment group (10% curry leaf extract), a positive control (metronidazole), and a negative control (aquades). The number of fibroblast cells was statistically assessed with the one-way ANOVA method and the LSD post-hoc test.Outcome: The results showed a significant difference in the number of fibroblast cells stimulated by periodontitis in each group.Conclusion: There was significant variance in fibroblast count between the groups.